The Analysis of Wonderful Indonesia Logo: Sanders Peirce's Triadic Theory - Kusumarini, Indah (e-Journal of Linguistics; Vol 15 No 2 (2021): e-jl JulyDO - 10.24843/e-jl.2021.v15.i02.p08, 2021)
The Wonderful Indonesia logo is an Indonesian tourism identity formed by verbal and non-verbal elements. The verbal element i s the words "wonderful Indonesia" and the non-verbal element i s a picture of "bird" such as the eagle which i s a symbol of the Indonesian state. Charles Sanders Peirce's Triadic theory mention s three main elements that make up the Wondeful Indonesia logo , namely : object, representation and interpretant.       The representation is expressed in the written language of “wonderful Indonesia” with artistic writing, flexible, elegant and beautiful fonts. It i s interpreted that Indonesia is one of the world's most beautiful, charming and enchanting tourist destinations. The writing of "Indonesia" is bigger than the word “ wonderful ” so that it is interpreted that Indonesia is the one that has a variety of charms. The object, in the form of a bird image, is like a Garuda. The head, wings, tail and body of the bird are displayed with flexible, beautiful, artistic lines, reflecting that Indonesians have a flexible, friendly, peace-loving character and are welcome to the world community.     The word "wonderful" i s written in English as  world’s of  language  It is hoped that this word which has a great, amazing, enchanting meaning can easily come to the citizen of world’s mind.. Based on the function of language, the word "wonderful" has a poetic function, which is a message to be conveyed to the world, that Indonesia is very charming, amazing, unique and interesting.